FRI0133 Central role of tocilizumab in fibroblast dominated models of inflammatory autoimmune arthritis. (12th June 2018) - Nielsen, M.A.; Deleuran, B.; Kragstrup, T.W.
Abstract : Background: Immune mediated inflammatory arthritis including rheumatoid arthritis (RA), psoriatic arthritis (PsA) and spondyloarthritis (SpA) all characterised by joint synovitis. Disease-modifying antirheumatic drugs (bDMARDs) targeting specific components of the pathogenesis have radically improved the treatment of the diseases. However, a fair proportion of patients are non-responders. Today, the first choice of DMARD is dependent on market pricing, regardless of the immunological target. This is due to the rather similar efficacy profile of the different DMARDs. Therefore, there is a need for stratification of patients suffering from Immune mediated inflammatory arthritis in order to reduce the fraction of DMARD non-responders. Objectives: The objective of this study was to study the effects of various DMARDs on different synovial cell subsets using several human ex vivo models of immune mediated inflammatory arthritis. This could potentially guide future studies of personalising DMARDs in these diseases. Methods: Synovial fluid was obtained from a study population of patients with active rheumatoid arthritis (RA) or peripheral spondyloarthritis (SpA). Synovial fluid mononuclear cells (SFMCs) containing primarily synovial monocytes and lymphocytes cultured for 48 hours (" Macrophage and Lymphocyte model" ) were used to study the effect of different biological agents on secretion of monocyte chemoattractant protein-1 (MCP-1) (n=14). Further, fibroblast-like synovial cells (FLSs) were co-cultured with autologous PBMCs (" FLS model" ) to study the effects of the same biological agents (n=6) in cultures dominated by synovial FLSs. Finally, SFMCs cultured for 21 days (" Osteoclast model" ) were studied to assess the effects on inflammatory osteoclastogenesis (n=10) measured by tartrate-resistant acid phosphatase (TRAP). The DMARDs investigated are shown in table 1. Results: "Macrophage and Lymphocyte model" ; In SFMCs cultured for 48 hours, all DMARDs included, except anakinra, had the ability to decrease the production of MCP-1. The two TNF inhibitors (adalimumab and etanercept) (p<0.05 and p<0.01) and baricitinib (p<0.05) had the most pronounced effects and reduced the production of MCP-1 by approximately 25%. Tocilizumab had in this culture a non-significant reduction of MCP-1 production. "FLS model" ; In the FLS+PBMCs cultured for 48 hours, tocilizumab (p<0.001) and the two JAK inhibitors (tofacitinib and baricitinib, p<0.05 and p<0.05) were exclusive in decreasing the cytokine production of MCP-1 by around 50%. "Osteoclast model"; In SFMCs cultured for 21 days, only the two TNF inhibitors, adalimumab and etanercept were able to significantly reduce the secretion of TRAP from adherent macrophage like synovial cells by roughly 25% (p<0.01, p<0.001). Conclusions: This study reveals that most DMARDs have effects in the " Macrophage and Lymphocyte model" whereas tocilizumab, tofacitinib and baricitinib were superior in the " FLS model" and only the two TNF inhibitors were effective in the " Osteoclast model". The findings in the " FLS model " reveals a possible beneficial effect of tocilizumab and JAK inhibitors to patients with fibroblast dominated arthritis. This study could potentially guide future studies of personalising DMARDs to treat immune mediated inflammatory arthritis. Disclosure of Interest: None declared